AOIR ETHICS PANEL 1: PRACTICES AND ROADMAPS - Vaughan, Antonia; Eneman, Marie; Hård af Segerstad, Ylva; Nilsson, Stefan; Olsson, Maria; Zheng, Tian; Zaugg, Isabelle; Reeve, Jonathan; Zimmer, Michael (AoIR Selected Papers of Internet Research, 2021)
This panel is one of two sessions organized by the AoIR Ethics Working Committee. It collects four papers exploring a broad (but shared) range of practices that present ethical challenges in internet research, while also providing possible roadmaps towards addressing these concerns. These include: the risks and challenges researchers face when researching far-right communities online; the ethical dilemmas faced when researching online sexual crimes involving children; the ethical grey zones researchers have to navigate when research environments fail to provide appropriate tools and protocols to keep pace with changing regulations; an analysis of data ethics syllabi in order to provide a framework to guide how we teach data and internet ethics. Taken together, the papers in this panel discussion engage with novel domains of internet research and shine a light on the unique ethical questions increasingly confronting researchers, while also striving to provide possible guidance on how to start addressing these dilemmas. These papers are among those under consideration for publication in a special issue of the Journal of Information, Communication and Ethics in Society associated with the AoIR Ethics Working Committee and AoIR2021.